The Gender Disclosure Gap: Salary History Bans Unravel When Men Volunteer Their Income - Cowgill, Bo; Agan, Amanda; Gee, Laura K. (Organization Science, 2024)
This study investigates whether the success of salary history bans could be limited by job-seekers volunteering their salaries unprompted. We survey American workers in 2019 and 2021 about their recent job searches, distinguishing when candidates were asked about salary history from when they were not. Historically well-paid workers may have an incentive to disclose, and employers who are aware of this could infer that nondisclosing workers are concealing low salaries. Through this mechanism, all workers could face pressure to avoid the stigma of silence. Our data shows a large percentage of workers (28%) volunteer salary history, even when a ban prevents employers from asking. An additional 47% will disclose if enough other job candidates disclose. Men are more likely than women to disclose their salaries unprompted, especially if they believe other candidates are disclosing. Over our 1.5-year sample covering jurisdictions with (and without) bans, unprompted volunteering of salary histories increased by about 6–8 percentage points. Funding: This work was supported by W.E. Upjohn Institute for Employment Research; Ewing Marion Kauffman Foundation (Emerging Scholars Program). Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.17384 .